CXCL1/CXCR2 signaling in pathological pain: Role in peripheral and central sensitization - Silva, Rangel L.; Lopes, Alexandre H.; Guimarães, Rafaela M.; Cunha, Thiago M. (Neurobiology of disease, 2017)
Pathological pain conditions can be triggered after peripheral nerve injury and/or inflammation. It is associated with plasticity of nociceptive pathway in which pain is prolonged even after healing of the injured tissue. Generally combinations of analgesic drugs are not sufficient to achieve selective palliation from chronic pain, besides causing a greater number of side effects. In order to identify novel alternatives for more effective treatments, it is necessary to clarify the underlying mechanisms of pathological pain. It is well established that there are two main components in pathological pain development and maintenance: (i) primary sensory neuron sensitization (peripheral sensitization), and (ii) central sensitization. In both components cytokines and chemokines act as key mediators in pain modulation. CXCL1 is a chemokine that promote both nociceptor and central sensitization via its main receptor CXCR2, which is a promising target for novel analgesic drugs. Here, we reviewed and discussed the role of the CXCL1/CXCR2 signaling axis in pathological pain conditions triggered by either peripheral inflammation or nerve injury.